Quantitative Microstructure Characterization of Ag Nanoparticle Sintered Joints for Power Die Attachment - Wang, Yun; Li, Jianfeng; Agyakwa, Pearl; Johnson, Christopher Mark; Li, Shuguang (Molecular Crystals and Liquid Crystals, 2014)
© 2014 Copyright © Taylor & Francis Group, LLC. The samples of sintered Ag joints for power die attachments were prepared using paste of Ag nanoparticles at 240°C and 5 MPa for 3 to 17 minutes. Their microstructural features were quantitatively characterized with scanning electronic microscopy, transmission electron microscopy, X-ray diffraction and image analysis method. The resulting normalized thickness, pore size and porosity decreased, and grain size increased with increasing the sintering time. A time dependence of the form t1/n with n close to 2 or 3 can be further derived for the kinetics of the thinning, densification and grain growth within the sintered Ag joints.
Keywords: Sintering of Ag nanoparticles; Power die attachment; Image analysis method; X-ray Scherrer method; Kinetics of sintering